HEALTHY LIFE WITHOUT SMOKING : CAMPAIGN - Didiek Hardiyanto Soegiantoro; Wirany Djangga Uma; Tesalonika Anindya Erna; Fidya Felicia Adelheid Tataung; Marna Kusumiati; Anggriana Rambu Gadi Mayi; Cindy Samosir; Elisa Stanley Giara (Journal of Innovation Research and Knowledge, 2022)
Smoking has become a necessity and lifestyle of the Indonesian people. The prevalence of smokers in Indonesia is dominated by men ranging from children, adolescents, to adults and even the elderly. Cigarettes are one of the main causes of health problems in Indonesia, therefore the government has sought various ways to suppress the use of cigarettes, including the imposition of taxes and providing pictorial warnings on cigarette packs. This activity aims to educate the public about the dangers of smoking so that it is hoped that individual awareness will arise to stop smoking. The method used is to distribute illustrated leaflets in the zero point area of Yogyakarta on Saturday night. The results of this engagement activity reached the target of 1000 people with positive responses. Most of the target respondents did not know about the dangers of smoking, which could be seen from their body language reactions when reading leaflets. The conclusion of this activity is that the public still needs additional direct education about the dangers of smoking and it is not enough to use pictorial warning signs on cigarette packages.